Aplicação de métodos quantitativos de mapeamento de deslizamento de terra nas encostas de Vitória, ES - Ferrão, Guilherme Ventorim (2016)
The city of Vitoria, capital of Espirito Santo, has geotechnical characteristics, climatic and occupancy conditions in which propitiates landslide occurrences. This research contemplates the use of quantitative techniques to improve the analysis of susceptibility, hazard and risk in the city of Vitoria – ES. Decision making techniques such as Analytic Hierarchy Process (AHP) has been incorporated and the factors of landslide were judged and classified by degree of importance. Twenty one sectors have been selected in the neighborhood of Forte São João to be classified according to hazard and risk of landslide. The sector’s danger approach differed by the influence of instability of features in the sectors. However for all checks carried out, 60% or more sectors had the same hazard classifications or more conservative (overestimated assessment) than those classified by Mapenco and PMRR. This methodology allows prioritization of the evaluated sectors to be intervened by the government. Moreover, two maps of landslide susceptibility have been elaborated associating retro-analysis and AHP Method in GIS (Geographic Information System). These maps have been developed with the characteristics of the landslides occurred in the neighborhood Forte São João since 2006. These maps are discriminated by the conditioning factors of instability class division method. These were compared with local maps, prepared by Mapenco and PMRR with assessments in the field, and there was a similarity in susceptibility rating on approximately 60% of the physical area of the study.